Racial discrepancies in the association between paternal vs. maternal educational level and risk of low birthweight in Washington State - Ko Cynthia W; Nicolaidis Christina; Saha Somnath; Koepsell Thomas D (BMC, 2004)
Abstract Background The role of paternal factors in determining the risk of adverse pregnancy outcomes has received less attention than maternal factors. Similarly, the interaction between the effects of race and socioeconomic status (SES) on pregnancy outcomes is not well known. Our objective was to assess the relative importance of paternal vs. maternal education in relation to risk of low birth weight (LBW) across different racial groups. Methods We conducted a retrospective population-based cohort study using Washington state birth certificate data from 1992 to 1996 (n = 264,789). We assessed the associations between maternal or paternal education and LBW, adjusting for demographic variables, health services factors, and maternal behavioral and obstetrical factors. Results Paternal educational level was independently associated with LBW after adjustment for race, maternal education, demographic characteristics, health services factors; and other maternal factors. We found an interaction between the race and maternal education on risk of LBW. In whites, maternal education was independently associated with LBW. However, in the remainder of the sample, maternal education had a minimal effect on LBW. Conclusions The degree of association between maternal education and LBW delivery was different in whites than in members of other racial groups. Paternal education was associated with LBW in both whites and non-whites. Further studies are needed to understand why maternal education may impact pregnancy outcomes differently depending on race and why paternal education may play a more important role than maternal education in some racial categories.